Analysts versus the random walk in financial forecasting: Evidence from the Czech National Bank's Financial Market Inflation Expectations Survey - Kamil Kladívko; Pär Österholm (Örebro University School of Business, 2022)
In this paper, we analyse how financial market analysts' expectations in the Czech National Bank's Financial Market Inflation Expectations survey perform relative to the random-walk forecast when it comes to predicting five financial variables. Using data from 2001 to 2022, our results indicate that the analysts are able to significantly outperform the random-walk forecast for the repo rate and Prague Interbank Offered Rate at the onemonth forecasting horizon. For the five-year and ten-year interest rate swap rate, the random walk significantly outperforms the analysts at both the one-month and one-year forecasting horizons. For the CZE/EUR exchange rate, no statistically significant differences in forecast precision were found.
Keywords: E47; G17; 330; Survey data; Out-of-sample forecasts; Exchange rates; Interest rates